Kepemilikan Manajerial Memoderasi Hubungan Green Accounting dan Environmental Performance terhadap Economic Performance pada Perusahaan Konsumsi Makanan dan Minuman - Eveline Meisya; Holiawati Holiawati; Nofryanti Nofryanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The purpose of this study was to examine managerial ownership to moderate the relationship between green accounting, and environmental performance on economic performance in the food and beverage consumption sector. This type of research is associative quantitative. This study covers the category of food and beverage consumption companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling technique to obtain a sample of 13 companies. Use data analysis tools using Eviews. The data source is secondary data. The method used to analyze the data is panel data regression analysis. The results showed that green accounting has an influence on economic performance. Environmental performance has no influence on economic performance. Managerial ownership weakens the effect of green accounting on economic  performance, managerial ownership strengthens environmental performance on economic performance. The results showed that green accounting positively influences economic performance, highlighting the value of environmental cost management and reporting for businesses in enhancing profitability and operational efficiency. However, environmental performance was found to have no significant effect on economic performance in this sector, suggesting that merely implementing sustainable practices may not directly translate into financial gains unless supported by strategic financial reporting and green accounting measures. Interestingly, the study also found that managerial ownership has a moderating effect. Specifically, managerial ownership weakens the effect of green accounting on economic performance, possibly due to potential conflicts of interest or risk aversion among managers with significant stakes in the company. On the other hand, managerial ownership strengthens the relationship between environmental performance and economic performance, as managers are more likely to ensure that environmental strategies are aligned with long-term financial goals.